PERIOPERATIF ANESTESI TINDAKAN TURP PADA PASIEN GERIATRI DENGAN ANODONTIA - Muhammad Dwi Satriyanto; Irwandi Samosir (LPPM Universitas Abdurrab, 2023)
Perioperative anesthesia is the management before, during, and after surgery. In geriatric patients, perioperative anesthesia management considers age and changes that occur in physiological aging, including decreased organ function, systemic abnormalities, and including anodontia. Transurethral Resection of Prostate (TURP) is a prostate resection procedure that uses endoscopy, such as BPH (Benign Prostatic Hyperplasia) or Prostate cancer. A 65-year-old geriatric man with suspected prostate cancer came to the emergency room with the initial complaint of not being able to urinate since 1 week before entering the hospital, and had done TURP with regional anesthesia.